2019
DOI: 10.1002/admi.201901628
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar and Robust WSe2 Field‐Effect Transistors Utilizing Self‐Assembled Edge Oxides

Abstract: Transition metal oxides (TMOs) with high work function (WF) show promising properties as unipolar p-type contacts for transition metal dichalcogenides. Here, ambipolar field-effect transistors (FETs) enabled by bilayer WSe2 with self-assembled TMOs (WO2.57) as contacts are reported. Systematic material characterizations demonstrated the formation of WO2.57/WSe2 heterojunctions around nanoflake edges with Se atoms substituted by O atoms after air-exposure, while pristine properties of WSe2 almost sustained in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
(126 reference statements)
3
13
0
Order By: Relevance
“…The ongoing development of advanced Si microelectronics is being hindered by the scaling limits . To overcome this restriction, van der Waals (vdW) semiconductor materials with reduced dimensionality have been proposed. Among them, two-dimensional (2D) transition-metal dichalcogenides (TMDs) and black phosphorus with thickness-dependent energy bandgaps present intriguing electrical and optoelectronic properties with the potential for diverse application in devices such as diodes, field-effect transistors (FETs), heterojunction bipolar transistors, chemical/optical/mechanical sensors, and photovoltaic devices. Direct-to-indirect bandgap transitions and quantum confinement structures can be fabricated using 2D materials. Existing semiconductor materials include limitations in the heteroepitaxial growth due to a lattice mismatch. However, these limitations can be overcome in 2D vdW materials, which do not require the use of high-vacuum facilities for building heterostructures.…”
mentioning
confidence: 99%
“…The ongoing development of advanced Si microelectronics is being hindered by the scaling limits . To overcome this restriction, van der Waals (vdW) semiconductor materials with reduced dimensionality have been proposed. Among them, two-dimensional (2D) transition-metal dichalcogenides (TMDs) and black phosphorus with thickness-dependent energy bandgaps present intriguing electrical and optoelectronic properties with the potential for diverse application in devices such as diodes, field-effect transistors (FETs), heterojunction bipolar transistors, chemical/optical/mechanical sensors, and photovoltaic devices. Direct-to-indirect bandgap transitions and quantum confinement structures can be fabricated using 2D materials. Existing semiconductor materials include limitations in the heteroepitaxial growth due to a lattice mismatch. However, these limitations can be overcome in 2D vdW materials, which do not require the use of high-vacuum facilities for building heterostructures.…”
mentioning
confidence: 99%
“…In related work, Xu et al utilized WO x as contacts in bilayer WSe 2 FETs, where they argued that the substoichiometric, high work function WO 2.57 offered decreased contact resistance and enhanced channel current, with conductivities as high as 2600 S m –1 . In line with these experimental results, DFT calculations showed that the substoichiometric oxide formed through air exposure gives rise to a defect band near the Fermi energy, resulting in gap-state-assisted carrier transport and enhanced conductivities …”
Section: Oxidation-based Morphotaxymentioning
confidence: 92%
“…Considering the almost half-a-trillion-dollar semiconductor-chip market, two-dimensional (2D) materials are currently one of the most feasible and promising candidates for extending Moore's law [1][2][3][4][5]. As a representative member of the 2D family, transition metal dichalcogenides (TMDs) have been intensively studied due to their distinctive optoelectronic properties and potential applications [6][7][8][9][10][11][12] in photodetection and lightemitting devices [13,14]. Notably, the tunable bandgap, high carrier mobility, high optical absorption and atomically thin thickness, making TMDs appropriate channel materials for photodetectors, play a crucial role in optoelectronic or electronic devices [15,16].…”
Section: Introductionmentioning
confidence: 99%